2012
DOI: 10.1016/j.intimp.2012.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Anthraquinone derivative O,O′-bis-(3′-iodopropyl)-1,4-dihidroxyanthraquinone modulates immune response and improves experimental autoimmune encephalomyelitis

Abstract: The present study investigated the effects of the anthraquinone derivative (O,O'-bis-(3'-iodopropyl)-1,4-dihidroxyanthraquinone - DIPDHAQ), mitoxantrone analog, in an experimental autoimmune encephalomyelitis (EAE) model. The results showed that DIPDHAQ treatment improved the clinical signs of the disease (n=10; vehicle: 3.8 ± 0.3; DIPDHAQ: 1.4 ± 0.9). The improvement was associated with a decrease of inflammatory cells, demyelination, IL-17, IFN-γ, IL-12p40, IL-6, TGF-β, CCL5 and CCL20 levels in the spinal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…reduced the production of IFN-γ and IL-12 approximately by 25% and 60%, respectively. 43 In the present study, intravenous injection with NHNK (twice a week for 3 weeks) declined mean clinical score by 20% and reduced the production of IFN-γ and IL-12 by 50% and 20%, respectively. On the basis of these results, we speculate that the efficacy of intravenous NHNK therapy against EAE may be comparable to that of fingolimod and mitoxantrone.…”
Section: Nhnk Alleviated the Infiltration Of Th1 Cells Into The Spinasupporting
confidence: 49%
“…reduced the production of IFN-γ and IL-12 approximately by 25% and 60%, respectively. 43 In the present study, intravenous injection with NHNK (twice a week for 3 weeks) declined mean clinical score by 20% and reduced the production of IFN-γ and IL-12 by 50% and 20%, respectively. On the basis of these results, we speculate that the efficacy of intravenous NHNK therapy against EAE may be comparable to that of fingolimod and mitoxantrone.…”
Section: Nhnk Alleviated the Infiltration Of Th1 Cells Into The Spinasupporting
confidence: 49%
“…First, EAE was induced in C57Bl/6 mice and splenocytes were obtained after 20 days of MOG 35–55 immunization, because according to literature[18,19] the maximum immune response occurs around day 17 until 20 after induction of EAE. Then, the spontaneous or stimulated (ConA and MOG 35–55 ) production of both oxygen radicals (H 2 O 2 and NO) and cytokines (TNF‐α, IFN‐γ and IL‐17) was analysed after in‐vitro incubation with LicoA (at non‐cytotoxic concentrations).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that IFN‐γ (Th1 cytokine), IL‐17 (Th17 cytokine) and TNF‐α play important roles in the induction and severity of MS and EAE [7,19,30]. During the acute phase of EAE, IFN‐γ and TNF‐α appear, and the level of expression parallels the severity of clinical signs and degree of inflammatory cells infiltration [31,32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations